Microstructure and texture development in CoCrNi medium entropy alloy processed by severe warm cross-rolling and annealing. (April 2022) - Saha, J.; Saha, R.; Bhattacharjee, P.P.
Abstract: The effect of cross-rolling on microstructure and texture evolution in equiatomic CoCrNi medium entropy alloy (MEA) was investigated in the present work. For this purpose, the MEA was warm-rolled to 90% reduction in thickness at 400 °C by unidirectional and different cross-rolling routes. The heavily deformed specimens were further annealed at temperatures varying from 700 °C to 1200 °C. The development of fine-scale microstructures and profuse shear band formation was confirmed in all the processed materials. Compared to unidirectional processed material, the different cross-rolled materials showed greater propensity for forming intersecting shear bands. Higher hardness in the different cross-rolled materials was consistent with finer microstructure and abundant shear bands. Unidirectional processed material showed weak brass (110<112>) component, whereas the different cross-rolled material showed rotated brass components. Upon annealing, the different cross-rolled materials showed smaller grain sizes than the unidirectional processed material due to more abundant potential nucleation sites. The recrystallization texture of the different processed materials showed retention of the deformation texture components. High fractions of random components indicated weak recrystallization texture, contributed by the absence of preferential nucleation and growth and profuse annealing twin formation. Highlights: Warm cross-rolling and annealing behavior of CoCrNi investigated. Profuse intersecting shear bands in different cross-rolled materials. Development of rotated-brass texture after cross-rolling. Smaller grain size and weak recrystallization texture in cross-rolled materials. Considerable effect of cross-rolling on microstructure and texture formation.